Keistimewaan Kurma Dalam Al-Qur’an ditinjau Dari Perspektif Ilmu Kesehatan.: Keistimewaan Kurma Dalam Al-Qur’an ditinjau Dari Perspektif Ilmu Kesehatan. - Ahfira Puteri (JURNAL KESEHATAN : JURNAL ILMU- ILMU KEPERAWATAN, KEBIDANAN, FARMASI DAN ANALIS KESEHATAN, SEKOLAH TINGGI KESEHATAN MUHAMMADIYAH CIAMIS, 2022)
The specialty of dates compared to other fruits is very much and has a fairly high benefit to us as humans in spiritual and physical aspects. As Allah SWT tells in the Al-Quran Al-'Azim the incident of Maryam when she wanted to give birth. In a health science approach, the authors found that dates are nutritious, the various vitamins and minerals contained in them can cure various diseases because all of these ingredients are antidotes or drugs. The purpose of this study is to discuss the hadith of dates as an alternative in increasing immunity during the Covid-19 period. This study uses a qualitative approach through literature study by applying the method of takhrij hadith and syarah hadith. As for the interpretation used analysis of contemporary issues, the results of this study found that the quality status of the hadith about dates is considered valid according to takhrij hadith. Meanwhile, the hadiths show that dates are known to be useful for increasing immunity during the Covid-19 pandemic. The conclusion of this study is that the hadith about dates can be referred to as an Islamic practice because it has a valid status and dates can be used to increase immunity during the Covid-19 pandemic according to health sector instructions.